Dichlorvosâ€induced oxidative stress in rat brain: Protective effects of the ethanolic extract of Alstonia boonei stem bark - Ojo, Mr. Oluwafemi Adeleke (Asian Journal of Pharmaceutics (AJP), 2014)
Organophosphorous pesticides, commonly used in agriculture for achieving betterâ€quality products, are toxic substances that have harmful effects on human health. Recent research on pesticides, especially pesticide mixtures, has shown that they are one of the key environmental health issues. The aim of the present study was to investigate the protective effects of Alstonia boonei ethanolic extract in dichlorvosâ€induced neurotoxicity in Wistar rats. Dichlorvos (50 mg/kg body weight) wasÂ orally administered in Wistar rats for 14 days followed by the treatment of Alstonia boonei (200 and 400 mg/kg body weight) for 14 days. The activities of lipid peroxidation (LPO), reduced glutathione (GSH) and activities of antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), alanine aminotransferase (ALT) andÂ aspartate aminotransferase (AST) level were measured to evaluate the toxicity of these pesticides in the brain. HistologicalÂ examinations of the brain were monitored. Under the influence of dichlorvos, there was significant decrease in the activitiesÂ of SOD, CAT, GPx, GSH, ALT and AST and significant increase in malondialdehyde. Alstonia boonei showed a significantÂ brainâ€protective effect by decreasing the level of lipid peroxidation and elevating the activities of antioxidative enzymesÂ and the level of GSH. Furthermore, histological alterations in the brain were observed in dichlorvosâ€untreated rats andÂ were ameliorated in dichlorvosâ€induced treated rats with Alstonia boonei. The observations presented lead us to concludeÂ the harmful effects of dichlorovos during the exposure and the protective role of Alstonia boonei in minimizing these effects. Key words: Alstonia boonei, brain, dichlorvos, lipid peroxidation, organophosphate, oxidative stress, reactive oxygen species